Enhancement of Channel Assignment Based on BPSO Algorithm in Multi-Radio Multi-Channel Wireless Mesh Networks - Kaur, G; Saini, J.S (International Journal of Computer Sciences and Engineering, 2025)
The Multi-Radio Multi-Channel Wireless Mesh Network (MRMC WMN) is an emerging technology for promoting a variety of applications. In this paper, the issues of channel assignment have been studied in which channels are assigned to different links and enhance the entire network performance. For MRMC WMN, the issue of channel assignment proved to be NP-complete. In this paper, joint Binary swarm optimization technique (BPSO) and linear programming (LP) has been proposed, in which BPSO algorithm is used to solve the issue of channel assignment by using linear programming model. To deal with these issues, a linear objective function has been used in the BPSO algorithm to evaluate the fitness value of each particle. Moreover, a rate-variable model has been proposed to enhance the network performance, wherein the physical interference model has been used to assess the capacity of the network. The simulation results show that the proposed technique efficiently improve the network performance